2017
DOI: 10.1249/mss.0000000000001286
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Resistance Exercise on Muscle Metabolism and Autophagy in sIBM

Abstract: These results demonstrate that RE had a preventive effect on sIBM induced by CQ treatment in an animal model. However, because the results were from an animal experiment, a more detailed study should be conducted over a longer period, and the effectiveness of different RE programs should also be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 44 publications
5
19
0
Order By: Relevance
“…We found that CQ treatment significantly increased Aβ accumulation in SM, but not in FHL muscle (data not shown), which is in agreement with our and other previous studies [18, 24]. Importantly, this finding provides further evidence for why muscle atrophy was induced predominantly in SM.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We found that CQ treatment significantly increased Aβ accumulation in SM, but not in FHL muscle (data not shown), which is in agreement with our and other previous studies [18, 24]. Importantly, this finding provides further evidence for why muscle atrophy was induced predominantly in SM.…”
Section: Discussionsupporting
confidence: 93%
“…These findings indicated that PINK1/parkin-mediated activation of mitophagy was blocked, which might be associated with CQ-induced Aβ accumulation, as suggested by the negative correlations between Aβ oligomers and mito-PINK1 and mito-parkin. Previous studies have suggested that physical exercise rescued impaired autophagy flux by CQ treatment in the brain and muscle [18, 27, 35], but the relationship between RE and CQ-induced abnormal mitophagy flux had not been demonstrated. Interestingly, RE dramatically reversed the levels of both proteins, thus likely restoring PINK1/parkin-mediated mitophagy initiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of exercise have been shown to be an autophagic inducer, cellular autophagic responses to exercise in skeletal muscle appear to be varied in different exercise protocols and disease models (Lenhare et al ; Jeong et al ). Exercise is the greatest physiological stress that our bodies experience.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent past (Lee et al 2013), it was demonstrated that exercise preconditioning reduces acute ischemic renal injury in HSP70.1 knockout mouse. The effects of exercise have been shown to be an autophagic inducer, cellular autophagic responses to exercise in skeletal muscle appear to be varied in different exercise protocols and disease models (Lenhare et al 2017;Jeong et al 2017). Exercise is the greatest physiological stress that our bodies experience.…”
Section: Discussionmentioning
confidence: 99%